Inserção curricular da Agroecologia no município de Santa Cruz Cabrália, Bahia: desafios e possibilidades - Botter, Letícia Teles (2024)
Guided by a holistic and decolonial perspective, this dissertation investigated how the process of curricular insertion of Agroecology took place in the rural schools of the municipal network of the municipality of Santa Cruz Cabrália/BA, its challenges, the first steps taken and the possibilities and potentialities of this event. For this, it was important to highlight concepts such as Critical Environmental Education, Popular Education and Rural Education; the transition to Sustainable Societies; and the cultural, social and ethical principles involved in Agroecology itself as a science and practice. The use of the case study methodology, participant observation and semi-structured interviews were important to understand which actors proposed the curricular insertion of Agroecology in the municipality, how this occurred and if the process is taking place in order to meet the needs and wants of the different peasantry that make up the reality of Cabrália. The greatest challenges identified are to involve the populations in the construction of educational processes, consistent with their own realities and with critical, solidary and transformative purposes, as well as, for managers, to coordinate such processes from an institutional perspective. The training of educators in Agroecology, carried out with the MST and based on popular knowledge and praxis, was presented as a fundamental aspect for the consolidation of the curricular insertion of Agroecology in the territory.